The Mediating Effect of Vocabulary Knowledge on the Relationship Between Google Translate Usage and Writing Proficiency Among Grade 10 Students - Cueme, Ronald Jhon (International Journal of Educational Research Excellence, 2025)
Writing proficiency in English remains a significant challenge in the academic setting. This study explored how vocabulary knowledge mediates the relationship between Google Translate usage and writing proficiency. Mediation analysis was used to select 150 samples using a simple random sampling technique. The results revealed that the variable of interest did not significantly mediate the correlation between the predictive and criterion variables. This result challenged the proposition of the Technology-Enhanced Language Learning (TELL) framework. Further studies should explore other variables that mediate the link between Google Translate usage and writing proficiency. Additionally, educational institutions may introduce students to diverse technological tools to enhance their access to quality education, particularly in writing development.